Carbon Emission Reduction Potential through Sustainable Forest Management in Forest Concession of PT Salaki Summa Sejahtera, Province of West Sumatera - Iwan Hilwan; Andry Indrawan; Supriyanto; Teddy Rusolono (Jurnal Manajemen Hutan Tropika, 2012)
A management unit (MU) of a forest concession holder implementing the sustainable forest management (SFM) principles, could be involved in reducing Emmission from Reforestation and Forest Degradation (REDD+) and carbon trading project. The fact the strategic in implementing the REDD+ and carbon trading in MU level is still lack of pilot project and methodology. Therefore, some scenarios must be developed and tested to find out the best potential of carbon credit in MU level. The objectives of the research were: to calculate carbon credit in some SFM scenarios, to analyze of carbon trading project feasibility, and to determine carbon stock recovery period of logged over area (LOA). The result revealed that carbon stock and carbon credit of LOA was affected by timber cutting intensity. The 6th scenario with lowest annual allowable cutting (AAC) obtained greater carbon credit and profit coming from timber harvesting income and carbon trading. In other hand, this scenario has shortest duration of carbon stock recovery period (27 years) and shorter than its cutting cycle. In this case, the MU has to recalculate and to decrease its AAC to have highest benefits from carbon trading in the same cutting cycle period. It will provide double benefits from carbon trading, those are contribution in achieving the SFM purposes (production, ecology, social) and climate change mitigation.